Socialization Of Financial Literacy During The Covid-19 Pandemic In South Tanggerang MSME Gallery - Lisna Jayanti (Perhimpunan Sarjana Ekonomi dan Bisnis, 2022)
This service is entitled Socialization of Financial Literacy in the Era of the Covid-19 Pandemic to the Garri MSMEs in South Tangerang, Banten. The general objective of this community service activity is to provide practical training and knowledge of financial management which has an impact on the welfare of the community. The method used is a survey method and direct material delivery as well as simulations and discussions on management, financial management, increasing income and online loans that have an impact on the welfare of the community. The conclusion of this community service is that there will be assistance in management in financial management. The socialization was carried out by after the presenters explained the concept of family financial management accompanied by examples of financial calculations in the family, the participants were able to understand well, at which time the participants were able to make cash flow for their respective families' finances and were able to manage it well. . The training participants have been able to properly manage and manage family finances during the Covid-19 pandemic according to the theory.